Risperidone-Induced Neutropenia in a Schizophrenic Patient: A Case Report and Literature Review. (17th August 2021) - Atolagbe, Ayodele; Nkemjika, Stanley; Popoola, Olusegun; Oladeji, Oluwatoyin; Kogan, Irina; Saeed, Haroon; Olupona, Tolulope
Abstract : Neutropenia is an adverse effect of various pharmacological therapies, including antipsychotics. Among the second-generation antipsychotic (SGA) medications, clozapine is most notable for neutropenic adverse effect. Risperidone, another SGA drug, is linked mainly with metabolic adverse effects, but rarely, blood dyscrasia adverse reactions have been reported. Hence, we report the case of a 56-year-old African American woman who developed severe neutropenia following two weeks of oral risperidone treatment. Her neutrophil levels returned to normal limits following discontinuation of risperidone and switching to haloperidol.